PENYUSUNAN MODUL THE GREAT EMPLOYEE UNTUK MENINGKATKAN KETERIKATAN KERJA PADA PEGAWAI HOTEL âSâ - Hapsari, Prestisia Noviarta; Sinambela, Frikson Christian (University of Surabaya, 2016)
The purpose of this study are to prepare a set of âThe Great Employeeâ modules, as an effort to improve employeesâ work engagement and to assess the benefits of the modules that have been prepared. The subjects of this study were 10 employees of Hotel âSâ. The assessment method used was interviews. The sampling technique in this study was purposive sampling, where the sampling is based on the objectives and criteria. The result of this study shows that factors affecting work engagement within employees are meaning of work, self-efficacy, optimism, organizational citizenship behavior, social support, and performance feedback.